Research and optimization of the hand-over lifting mechanism of a sweet potato combine harvester based on EDEM - Shen, Haiyang; Wang, Bing; Wang, Gongpu; Wang, Yemeng; Bao, Guocheng; Hu, Lianglong; Hu, Zhichao (International Journal of Agricultural and Biological Engineering, 2023)
In order to meet the challenge of high loss rate and high tuber injury rate during the operation of the 4UZL-1 sweet potato combine harvester, the sweet potato tuber hand-over lifting mechanism was designed based on a comprehensive analysis of the entire structure of the harvester. Taking the average normal force on conveying sweet potato tubers as evaluation indexes, the EDEM simulation experiment was carried out considering the factors of the angle of the excavating and conveying mechanism, the conveying angle of the scraper chain, the speed of the excavating and conveying mechanism, and the speed of the scraper chain conveying. The experimental findings indicated that the optimal operational performance of the hand-over lifting mechanism was achieved at a speed of 1.15 m/s for the excavating and conveying mechanism, an angle of 24° for the excavating and conveying mechanism, a conveying speed of 0.66 m/s for the scraper chain, and a conveying angle of 60° for the scraper chain. Field experiments were conducted based on the EDEM simulation experiment, using the loss rate and the injury rate of conveying sweet potato tubers as evaluation indexes. The results showed that the hand-over lifting mechanism demonstrated optimal operational effectiveness with an excavating and conveying mechanism angle of 20°, a scraper chain angle of 68°, an excavating and conveying mechanism speed of 1.2 m/s, and a scraper chain speed of 0.66 m/s, while the machine running speed was maintained at 1 m/s. At the moment, the hand-over lifting structure exhibited a loss rate of 1.12% and a tuber injury rate of 0.94%. The conclusions obtained serve as a valuable reference for future research and optimization of sweet potato combines. Keywords: agricultural mechanization, sweet potato combine harvester, hand-over and lifting mechanism, EDEM simulation experiment, field experiment DOI: 10.25165/j.ijabe.20231605.7825 Citation: Shen H Y, Wang B, Wang G P, Wang Y M, Bao G C, Hu L L, et al. Research and optimization of the hand-over lifting mechanism of a sweet potato combine harvester based on EDEM. 2023; 16(5): 71–79